Improving small ruminant productivity: Genetic resources - Lethola, L.L. (1983)
The productive performances of Tswana and Boer goats, and Dorper sheep were investigated. Comparative performance on productivity per ewe/doe and young mortality in pure Tswana and Boer goats and Dorper sheep in Botswana were examined. The local breeds were superior for use in communal areas practising non-intensive husbandry.